2018
DOI: 10.1016/j.imbio.2017.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral vector-mediated GM-CSF gene transfer improves anti-mycobacterial immunity in mice – role of regulatory T cells

Abstract: Granulocyte macrophage-colony stimulating factor (GM-CSF) is a hematopoietic growth factor involved in differentiation, survival and activation of myeloid and non-myeloid cells with important implications for lung antibacterial immunity. Here we examined the effect of pulmonary adenoviral vector-mediated delivery of GM-CSF (AdGM-CSF) on anti-mycobacterial immunity in M. bovis BCG infected mice. Exposure of M. bovis BCG infected mice to AdGM-CSF either applied on 6h, or 6h and 7days post-infection substantially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…This result indicates that rapid response in HAM does occur but is limited to a smaller set of genes that in part differ from those in MDM at this early time point. GM-CSF in particular is a critical driver of HAM differentiation [ 46 48 ]. Defects in the GM-CSF pathway are associated with alveolar proteinosis and a propensity for mycobacterial infections [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…This result indicates that rapid response in HAM does occur but is limited to a smaller set of genes that in part differ from those in MDM at this early time point. GM-CSF in particular is a critical driver of HAM differentiation [ 46 48 ]. Defects in the GM-CSF pathway are associated with alveolar proteinosis and a propensity for mycobacterial infections [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports suggested that Tregs may have protective roles in models of acute lung injury (e.g., injury caused by LPS) and in models of chronic lung disease triggered by bleomycin or silica (15)(16)(17). Moreover, we recently found that Tregs actively suppress immunopathology in lung mycobacterial infections of mice (18). In addition, Tregs were found to suppress bronchiolitis obliterans in a mouse model of heterotopic bronchus transplantation as well as lung transplant arteriosclerosis in humanized mice (19,20).…”
Section: Regulatory T Cells Limit Pneumococcus-induced Exacerbation Of Lung Fibrosis In Micementioning
confidence: 70%
“…Lymphocytes were gated according to their FSC-A/SSC-A and CD45 cell surface expression, followed by identification of B cells based on their CD19 cell surface expression, whereas NK cells were NK1.1 pos and CD3 neg . T cell subsets were gated according to their CD45 pos /CD3 pos expression, whereas Tregs were identified according to their CD4 pos , CD25 pos and intracellular Foxp3 expression (18,21). T cells were further analyzed for their differential ab versus gd TCR expression profiles.…”
Section: Immunophenotypic Analysis Of Leukocyte Subsets In Bronchoalveolar Lavage Fluid and Lung Parenchymamentioning
confidence: 99%